Experimental Model to Test Electrostatic Precipitation Technology in the COVID-19 Era: A Pilot Study - Buggisch, Jonathan R. (J Am Coll Surg, 2020)
BACKGROUND: In the COVID-19 crisis, laparoscopic surgery is in focus as a relevant source of bioaerosol release. The efficacy of electrostatic aerosol precipitation (EAP) and continuous aerosol evacuation (CAE) to eliminate bioaerosols during laparoscopic surgery was verified. STUDY DESIGN: Ex-vivo laparoscopic cholecystectomies (LCs) were simulated ± EAP or CAE in Pelvitrainer equipped with swine gallbladders. Release of bioaerosols was initiated by performing high-frequency electrosurgery with a monopolar electro hook (MP-HOOK) force at 40 watts (MP-HOOK40) and 60 watts (MP-HOOK60), as well as by ultrasonic cutting (USC). Particle number concentrations (PNC) of arising aerosols were analyzed with a condensation particle counter (CPC). Aerosol samples were taken within the Pelvitrainer close to the source, outside the Pelvitrainer at the working trocar, and in the breathing zone of the surgeon. RESULTS: Within the Pelvitrainer, MP-HOOK40 (6.4 × 10(5) cm(-3)) and MP-HOOK60 (7.3 × 10(5) cm(-3)) showed significantly higher median PNCs compared to USC (4.4 × 10(5) cm(-3)) (p = 0.001). EAP led to a significant decrease of the median PNCs in all 3 groups. A high linear correlation with Pearson correlation coefficients of 0.852, 0.825, and 0.759 were observed by comparing MP-HOOK40 (± EAP), MP-HOOK60 (± EAP), and USC (± EAP), respectively. During ex-vivo LC and CAE, significant bioaerosol contaminations of the operating room occurred. Ex-vivo LC with EAP led to a considerable reduction of the bioaerosol concentration. CONCLUSIONS: EAP was found to be efficient for intraoperative bioaerosol elimination and reducing the risk of bioaerosol exposure for surgical staff.